Analisa Kebisingan di Bengkel Kerja Akademi Maritim Nusantara - Andi Hendrawan; Aji Kusumastuti Hendrawan (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2020)
One of the causes of occupational accidents and diseases is noise. High intensity noise that is not realized causes a serious impact on the workforce. Efforts for health and work safety must be made in order to minimize the impact and as much as possible do not cause accidents and illness due to work. This research aims to map the noise in the AMN workshop room . Type of Research This type of research is a type of survey research with a cross sectional Saund level approach to measure noise. Measurements are made in all rooms or places that are possible as places of activity. The measurement results show that it is still below the allowable threshold based on both the ILO Standards and the Government.